Conductivity enhancement of multiwalled carbon nanotube thin film via thermal compression method - Tsai, Wan-Lin (Springer, 2014)
For the first time, the thermal compression method is applied to effectively enhance the electrical conductivity of carbon nanotube thin films (CNTFs). With the assistance of heat and pressure on the CNTFs, the neighbor multiwalled carbon nanotubes (CNTs) start to link with each other, and then these separated CNTs are twined into a continuous film while the compression force, duration, and temperature are quite enough for the reaction. Under the compression temperature of 400°C and the compression force of 100 N for 50 min, the sheet resistance can be reduced from 17 to 0.9 k Ω/sq for the CNTFs with a thickness of 230 nm. Moreover, the effects of compression temperature and the duration of thermal compression on the conductivity of CNTF are also discussed in this work.